METODE IJTIHAD MAJELIS ULAMA INDONESIA (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2013)
Fatwa is believed to be a container having an important and significant role in the religious life of the Islamic community. The urgency and significance can be seen from its function as a mediating between the ideals of Islamic law on the one hand with the factual reality-communities on the other. This is where all the problems, concerns, hopes, aspirations and experiences presented and confronted people to look for common ground with the ideals of moral and religious ethics in Shari'ah mediated by the intellectual prowess of a mufti. One of the institutions that are semi-formal fatwa is the fatwa issued by the Fatwa Commission of the Indonesian Ulema Council (MUI), because these institutions are formally established by the government, but its provisions can not be forced as the decision of the judiciary. Since its establishment in 1975 MUI fatwa has been issued either at the request of individuals, community groups and at the request of the government. This simple article will try to look at and examine some of the MUI fatwa has been issued, to then be viewed and analyzed, especially in terms of legal istinbat method used in formulating his fatwa. Fatwa diyakini sebagai wadah yang memiliki peran penting dan signifikan dalam kehidupan beragama komunitas Islam. Urgensi dan signifikansinya terlihat dari fungsinya sebagai mediasi antara cita ideal hukum Islam di satu pihak dengan realitas-faktual masyarakat di pihak lain. Di sinilah setiap problem, keprihatinan, harapan, aspirasi dan pengalaman masyarakat disampaikan dan dikonfrontasikan untuk dicarikan titik temu dengan cita moral dan etika religius dalam syari’ah yang dimediasi oleh kecakapan intelektual seorang mufti. Salah satu lembaga fatwa yang bersifat semiformal adalah fatwa yang dikeluarkan oleh Komisi Fatwa Majelis Ulama Indonesia (MUI), karena lembaga ini resmi dibentuk oleh pemerintah, namun ketetapannya tidak dapat memaksa sebagaimana keputusan lembaga peradilan. Sejak berdiri tahun 1975, MUI telah banyak mengeluarkan fatwa baik atas permintaan individu, kelompok masyarakat maupun atas permintaan pemerintah. Tulisan sederhana ini akan mencoba untuk melihat dan meneliti beberapa fatwa yang telah dikeluarkan MUI, untuk kemudian dilihat dan dianalisis, terutama dari segi metode istinbat hukum yang digunakan dalam merumuskan fatwanya.